Evaluation of the Effectiveness of Online Training to Improve Lecturers’ Ability in E-Learning Management Using the Kirkpatrick Model - Dwikurnaningsih, Yari; Waruwu, Marinu (FKIP Universitas Lampung, 2022)
Social distancing causes lecturer training to be carried out online. Objectives: This study aims at the effectiveness of online training for lecturers in managing e-learning. This study uses an evaluation evaluation method with the Kirkpatrick model which includes evaluation of reactions, learning, behavior and results. Methods: The research approach is a mixed method with a sequential explanation model, where quantitative methods are used first and then qualitative methods are used in the next stage. Data collection techniques using questionnaires, and interviews. The research subjects are lecturers and students. Qualitative data were analyzed using the Miles and Huberman model and quantitative data were processed descriptively by calculating percentages and categorizing. Findings: The results showed that the reaction aspect was satisfied, learning was in the high category, behavior was in the moderate category and the results were in the good category. Conclusion: it works effectively, but needs improvement in the technical implementation of the training.Keywords: evaluation, e-training, Kirkpatrick, e-learningDOI: http://dx.doi.org/10.23960/jpp.v12.i2.202220